Evaluative practices and representation of the graduation profile in higher education teachers: Experiences in Education Faculties of Lima - Peru - Dávila Díaz, María Elena; Fernández Bringas, Teresa Cecilia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This study reveals the distance that exists between the evaluative practices of teachers and the graduation profile of students during the training action provided in Higher Education. Through a qualitative approach design, semi-structured interviews were conducted with professors from universities with Faculties of Education in Lima (Peru), who together with the graphic representations of their evaluative practice, reported that during the evaluation process the graduation profile is absent in the teacher’s eyes, which implies little assessment of this curricular component that is the guiding axis of the entire training process.